2012
DOI: 10.1007/s00428-012-1255-6
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of needle biopsies of the kidney for investigation of renal masses

Abstract: The development of new therapeutic options for renal tumors has lead to the need of a pretherapeutic diagnosis for an increasing proportion of patients presenting with a renal mass. This need is particularly important for a small, incidentally discovered renal mass (less than 4 cm) as it can be a benign lesion in a significant percentage of cases. Recent studies have shown that needle biopsy is an accurate and safe method allowing for a precise histopathological diagnosis of the mass in most cases. The aims of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Somewhat similar results have been reported in other recent series, indicating that the decisions about patient management based on radiological or clinical evaluations alone can get altered based on RCB findings. 11,17,19,24,25,34 Based on our study and the experience reported in recent series, percutaneous RCB can have a meaningful role in the management of renal tumors, including those with metastatic disease at presentation, while taking into account other clinical parameters.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Somewhat similar results have been reported in other recent series, indicating that the decisions about patient management based on radiological or clinical evaluations alone can get altered based on RCB findings. 11,17,19,24,25,34 Based on our study and the experience reported in recent series, percutaneous RCB can have a meaningful role in the management of renal tumors, including those with metastatic disease at presentation, while taking into account other clinical parameters.…”
Section: Resultssupporting
confidence: 53%
“…This is becoming increasingly important because the range of management options for renal neoplasms has increased in recent years. 11 Depending on the histologic subtype and malignant potential as determined on RCB, the clinical management varied significantly in our study. However, the biopsy diagnosis clearly did not influence the clinical management in 16 cases with relatively small tumors, in which the tumors were ablated at the same sitting as the biopsy procedure.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Some of those small renal masses do not present radiological criteria allowing determining the nature of these tumors. 15% to 35% of these incidentally discovered small renal masses are benign after final histological diagnosis [1]. A more precise pretherapeutic diagnosis is now required in order to avoid unnecessary surgical removal.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,23,46 Tumour cores should be fixed in 10% buffered formal saline with each core separated into individual cassettes. 47 The cores should be handled using a tissue conservation protocol with serial levels being obtained on microtomy. Charged slides should be used in case imunohistochemical stains are required.…”
Section: Tissue Core Handlingmentioning
confidence: 99%